The merger of Islamic banks and their impact on the stability of the country's economy - Pamungkas, Putra; Pratiwi, Desti Indah; Bakkar, Yassine (Universitas Sebelas Maret, 2022)
Mergers are familiar in economic terms, one of which is in the banking sector. Indonesia's banking sector adopting a dual banking system, namely the operation of conventional and Islamic banks, has caused the Indonesian people to have the choice to entrust their finances to one of the two types of banks. Not long ago, the Indonesian government announced that the three Islamic banks, which are part of the three conventional banks, would merge and change their name to Bank Syariah Indonesia (BSI). Of course, this decision is not easy, but it is a decision taken after careful consideration from the banking and economic perspective. Based on data from OJK, the total assets in the second quarter of Islamic banking in 2021 after the merger was recorded to have increased by 16.4 percent compared to the previous year’s period. This increase is in line with Bank Syariah Indonesia (BSI) financial report data in the first and second quarters, namely with second quarter total assets of 481 trillion rupiah and second quarter total liabilities of 435 trillion rupiahs. Based on these facts and data, this article aims to determine the impact of the merger of the three Islamic banks on the strengthening and stability of the Indonesian economy by comparing data from before and after the merger of Islamic banks in Indonesia.